2022
DOI: 10.1002/nau.25034
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pre‐ and postprostatectomy measures of pelvic floor muscle function and development of early incontinence after surgery

Abstract: Aims: The aim of this study is to investigate (i) whether pelvic floor muscle (PFM) shortening can be enhanced by provision of training focused on striated urethral sphincter (SUS) with feedback before prostatectomy, (ii) whether PFM shortening during voluntary efforts and coughing before and after prostatectomy differs between men who do and do not report symptoms of urinary incontinence 1 month after prostatectomy, and (iii) the relationship between severity of incontinence after prostatectomy and features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 34 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…After the screening of titles and abstracts, 14 articles remained. A full-text review revealed 13 articles that presented relevant data [16][17][18][19][20][21][22][23][24][25][26][27][28]. Two of the remaining articles contained overlapping data (confirmed by the authors) leading to one additional exclusion [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the screening of titles and abstracts, 14 articles remained. A full-text review revealed 13 articles that presented relevant data [16][17][18][19][20][21][22][23][24][25][26][27][28]. Two of the remaining articles contained overlapping data (confirmed by the authors) leading to one additional exclusion [28].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias assessment is summarised in Figure 2. The majority of the studies gave incomplete data on the characteristics of the study population [16,18,20,21,[24][25][26][27] and did not provide data on the recruitment period [16,18,20,[24][25][26][27], yielding potential bias. There was a significant risk of attrition bias in all of the studies, with inadequate reporting of response rate and no attempts to collect data on patients lost to follow-up or to consider the impact of attrition.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Behavioral therapy and physical therapy are still the main means ( Stafford et al, 2022 ). After RP an early supportive rehabilitation program like pelvic floor muscle training significantly reduces continence recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…PFMT, through targeted repetitive contractions, primarily strengthens the striated urethral sphincter, bulbocavernosus, and puborectalis—a component of the levator ani. This specific focus enhances urinary continence mechanisms in men, as extensively detailed in the body of work by Stafford and Hodges [ 11 , 12 , 13 ]. Consequently, PFMT increases the endurance and strength of the pelvic floor muscles, aiming to improve urinary, bowel, and sexual symptoms [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This specific focus enhances urinary continence mechanisms in men, as extensively detailed in the body of work by Stafford and Hodges [ 11 , 12 , 13 ]. Consequently, PFMT increases the endurance and strength of the pelvic floor muscles, aiming to improve urinary, bowel, and sexual symptoms [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%